Complete dentures over resorbed ridges: enhancing stability and esthetics with posterior platforms - Guilherme E. P. Henriques; Mauro A. A. Nóbilo; Marcelo F. Mesquita (Universidade Estadual de Campinas, 2015)
A modified teeth arrangement protocol and a procedure to incorporate posterior balancing platforms in complete dentures have been described. The use of platforms is an approach to achieving stability in dentures over resorbed residual ridges due to bilateral contacts in eccentric relations. Esthetic results are enhanced due to vertical overbite in centric and interocclusal distance in eccentric relations.